Extraction of effective mobility of In0.8Ga0.2As/In0.52Al0.48As quantum well high-electron-mobility transistors on InP substrate. (November 2022) - Park, Wan-Soo; Kim, Jun-Gyu; Yun, Seung-Won; Jeong, Hyeon-Seok; Jo, Hyeon-Bhin; Kim, Tae-Woo; Tsutsumi, Takuya; Sugiyama, Hiroki; Matsuzaki, Hideaki; Kim, Dae-Hyun
Abstract: In this work, we explored the effective mobility of In-rich In x Ga 1-x As/In 0.52 Al 0.48 As ( x  > 0.53) quantum well (QW) high-electron-mobility transistors (HEMTs) on an InP substrate. Historically, the carrier transport properties of these types of devices have been assessed mostly using their Hall mobility, not using the effective mobility, mainly because the excessive gate leakage current degrades and contaminates their measured capacitance voltage (CV) characteristics. However, our recent studies on these devices achieved a significant reduction in the gate leakage current, which motivated us to explore their effective mobility. In this work, therefore, we used a conventional split CV technique to determine and analyze the effective mobility of In 0.8 Ga 0.2 As/In 0.52 Al 0.48 As QW HEMTs. We also attempted to model the extracted effective mobility by considering three different scattering mechanisms—Coulombic scattering, phonon scattering and surface-roughness scattering— under the guidance of Matthiessen's rule.